Optimization of cell-free plasma RNA extraction for downstream application / Wan Alif Afiq Wan Nor Ruddin ...[et al.] - Wan Nor Ruddin, Wan Alif Afiq; Mohd Ridah, Lailatul Jalilah; Mohd Nor, Nurul Yaqin; Ismail, Hamizah; Zainuddin, Norafiza (Faculty of Applied Sciences, 2021)
The growing interest in biomedical studies has brought RNA from biofluids including plasma, as promising candidates for genetics profiling. The precision and reliability of an analysis in downstream application such as NanoString nCounter® MAX Analysis System (NanoString Technologies, Seattle, WA) ) depend on the RNA quality, purity and level. In this project, NanoString nCounter® miRNA panel was chosen due to rapid identification and ability to profile approximately 800 miRNAs per run which requires total RNAs from plasma with a minimum concentration of 33.3 ng/µL with 260/280 and 260/230 ratios of ≥1.8 for optimal results. Unlike tissues and cells, circulating RNAs in plasma are cell-free and are present in small sizes. However, the abundance of proteins and inhibitors in the plasma as possible contaminants could diminish the effectiveness of molecular isolation techniques and pose challenges in RNA isolation and quantification. This could skew data collection and elucidation. Therefore, the main objective is to determine the optimized plasma RNA isolation protocol to overcome problems in RNA quality and purity with regards NanoString nCounter® MAX Analysis System requirement. Several optimization steps were performed, including the addition of one chloroform extraction step with extra washing steps instead of conducting only once following the actual protocol. After conducting these steps, the average 260/280 ratio falls between 1.7 to 1.8, slightly increased compared to the results before optimization which was around 1.4 to 1.6 since these steps of optimization help to remove excess impurities including phenol and salt. Furthermore, increasing the incubation time in certain steps, for instance, after sample homogenization with Qiazol, during 95% ethanol precipitation and after RNase-free water addition have boosted the RNA recovery allowing RNA concentration of 15 ng/µL and above to be obtained. Hence, the optimized plasma RNA isolation protocol was determined since several issues related to plasma RNA concentration and purity were significantly improved by performing the additional steps in the protocol.